Estudos dos polimorfismos dos genes GSTT1, GSTM1 e NINJURIN1 em indivíduos com hanseníase - Graça, Carla Renata (2011)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae (M. leprae), an obligate intracellular acid-fast bacillus, which affects the skin and peripheral nervous system. The diseases expression results from the interaction between the bacillus and the immune system; most infected subjects develop effective immune response against M. leprae, without disease; others exhibit a spectrum of clinical manifestations closely linked to the pattern of host immune response to pathogen. Among the host defense mechanisms are immunoregulatory cytokines with activities represented by specific populations of Th1 and Th2 lymphocytes and the production of reactive oxygen species (ROS), which are key elements for bacterial destruction intramacrofágica. In this context, several genomic regions have been implicated in susceptibility and severity in genetically controlled leprosy. The glutathione Stransferase are enzymes that eliminate reactive oxygen species, are the most studied genes: GSTM1 and GSTT1. The NINJURIN1 is a cell adhesion molecule that provides suitable substrates for repair of Schwann cells after peripheral nerve injury. The single nucleotide polymorphism NINJ1, encoded by the protein NINJURIN1, is the result of a transversion to adenine nucleotide polymorphic cytokine (AC), responsible in an amino acid exchange of asparagine for alanine at position 110 of the protein (asp110ala). Objectives. 1) Investigate if the presence of polymorphism in the GSTT1 and GSTM1 genes could affect the course of leprosy; 2) Investigate if the presence of polymorphism in the NINJ1 gene could be relevant for neural impairment. Material and Methods. A cohort of 218 leprosy patients (patients) and 244 subjects without leprosy (controls) was studied. The genomic DNA was obtained from peripheral blood, GSTT1 and GSTM1 polymorphism screening was performed using polymerase chain. Abstract v reaction and NINJ1 gene analysis was performed using the technique of restriction fragment length polymorphism (PCR-RFLP) using the enzyme Hae III. The genotype and allele frequency were measured by Chi-square and logistic regression models with or without correction for age and gender. Results. The frequency of the GSTT1/GSTM1 null genotypes was significantly higher in controls when compared to patients (P = 0.01). The GSTT1 genotype frequency was significantly increased in patients when compared to controls (P=0.01). The frequency of the NINJ1 asp110ala was significantly increased in patients with nerve impairment (p = 0.0198). Also, patients with the CC (ala/ala) allele had a higher risk of developing disability when compared the allele AA (asp/asp) (p = 0.0143). Conclusion. The results demonstrated: (1) there is an association of GSTT1 positive genotype for development of leprosy disease. The data found suggested that the absence of GSTs, with a consequent permanence of intracellular ROS, can contribute to M. leprae destruction and, therefore, reduce the disease risk; (2) polymorphism in NINJ1 gene offers less nerve protection in leprosy patients. This finding indicates that NINJURIN1 is an important adhesion molecule and can be a potential therapeutic tool in many diseases.